Peningkatkan Hasil Belajar Peserta Didik Kelas V Sd N 2 Prambanan Dengan Model Project Based Learning (PJBL) - Rahmawati, Isna; Rofisian, Nela; Ferryka, Putri Zudhah; Suwartini, Sri (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study aims to investigate the improvement of learning outcomes among fifth-grade students at SD Negeri 2 Prambanan through the implementation of the Project Based Learning (PjBL) model. The background of this research is the low academic performance of students, with 61% of them scoring below the Minimum Mastery Criteria (KKTP). This condition is attributed to the lack of innovative teaching strategies, making it difficult for students to comprehend the subject matter. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The subjects of the study were all students in class V-B of SD Negeri 2 Prambanan, totaling 18 students (9 male and 9 female). Data were collected using observation sheets, learning outcome tests, and documentation. The data were analyzed descriptively by reflecting on the outcomes of each action cycle. The findings indicate an improvement in students’ learning outcomes across the cycles. The average score increased from 74.87 in the pre-cycle to 77.33 in the first cycle, and further to 80.11 in the second cycle. The percentage of students achieving mastery increased from 38.9% in the pre-cycle to 66.67% in the first cycle, and to 88.89% in the second cycle.These results demonstrate that the implementation of the Project Based Learning model effectively enhances the learning outcomes of fifth-grade students at SD Negeri 2 Prambanan.